Hypokalemia, how to clarify and treat: a review article - Paramita Dwisari Putri, Luh Ayu Made; Suryana, Ketut (International Journal of Advances in Medicine, 2023)
Hypokalemia is a frequent electrolyte disturbance in clinical practice and in hospitalized patients. Potassium disturbances are common and have been associated with increased mortality in several populations. The incidence of hypokalemia often occurs refractory and without a clear cause so very difficult to prevent and can increase risk of recurring conditions and require treatment. Through this overview will discuss what are the underlying causes of hypokalemia and what tests are needed to find out the cause of hypokalemia so that it can remind health worker and to prevent recurrence of emergencies conditions due to hypokalemia. The type of study is used literature review. In addition, the purpose of this study method is to reveal various theories that are relevant to the diagnostic approach to determine the causes of hypokalemia so that it can be used as reference material in daily practice. Hypokalemia is usually a sign of various diseases that can cause emergency conditions. If the cause is not known for certain, it will cause recurrent hypokalemia. It is important for health workers to conduct interviews to find out the patient's medical history, physical examination and comprehensive supporting examinations to determine the cause of hypokalemia. Comprehensive management is needed and must be done immediately so that the condition of hypokalemia does not lead to emergency conditions. In some patients, such as in endocrine related hypokalemia cases, multidisciplinary diagnostic and therapeutic approach is needed.